2022
DOI: 10.3389/fpubh.2022.916364
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Model for Colon Adenocarcinoma Patients Based on Ten Amino Acid Metabolism Related Genes

Abstract: BackgroundAmino acid metabolism plays a vital role in cancer biology. However, the application of amino acid metabolism in the prognosis of colon adenocarcinoma (COAD) has not yet been explored. Here, we construct an amino acid metabolism-related risk model to predict the survival outcome of COAD and improve clinical decision making.MethodsThe RNA-sequencing-based transcriptome for 524 patients with COAD from The Cancer Genome Atlas (TCGA) was selected as a training set. The integrated Gene Expression Omnibus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…The human ribosomal protein RPS17 plays an important role in several diseases. The mutations in the ribosomal protein S17 (RPS17) gene are closely associated with hereditary bone marrow failure syndrome 47 , while it has also been shown that RPS17 may affect CRC prognosis by controlling amino acid metabolism 48 , which is consistent with our study. The heat shock protein family A member 1A (HSPA1A) belongs to the heat shock protein 70 family.…”
Section: Discussionsupporting
confidence: 91%
“…The human ribosomal protein RPS17 plays an important role in several diseases. The mutations in the ribosomal protein S17 (RPS17) gene are closely associated with hereditary bone marrow failure syndrome 47 , while it has also been shown that RPS17 may affect CRC prognosis by controlling amino acid metabolism 48 , which is consistent with our study. The heat shock protein family A member 1A (HSPA1A) belongs to the heat shock protein 70 family.…”
Section: Discussionsupporting
confidence: 91%
“…The nomogram also had a high C-index and accuracy. Compared with earlier research (Ren's 10-gene signature), our signature's 5-years AUC was higher than Ren's and was more concise with only five genes (Ren et al, 2022). These outcomes indicated our model was robust and performed well in predicting the survival of colorectal cancer patients.…”
Section: Discussionmentioning
confidence: 48%
“…ANXA5, serving as a marker for macrophage subsets, could predict immune therapy responses in endometrial cancer [ 58 ]. GAMT served as one of the components to predict the sensitivity of colorectal adenocarcinoma patients to immune therapy targeting PD-1 and CTLA-4 [ 59 ]. The downregulation of SLC7A2 upregulated CXCL1 through the PI3K/Akt/NF-κB pathway, recruiting bone marrow-derived suppressor cells and exerted a tumor immune inhibitory effect [ 60 ].…”
Section: Discussionmentioning
confidence: 99%